2011
DOI: 10.1371/journal.pone.0027864
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of Antiretroviral Therapy with a CCR5 Antagonist in Patients with Chronic HIV-1 Infection: Effect on T Cells Latently Infected

Abstract: ObjectiveThe primary objective was to assess the effect of MVC intensification on latently infected CD4+ T cells in chronically HIV-1-infected patients receiving antiretroviral therapy.MethodsWe performed an open-label pilot phase II clinical trial involving chronically HIV-1-infected patients receiving stable antiretroviral therapy whose regimen was intensified with 48 weeks of maraviroc therapy. We analyzed the latent reservoir, the residual viremia and episomal 2LTR DNA to examine the relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 47 publications
5
64
1
Order By: Relevance
“…The decrease of D dimer levels which have been associated with lower cardiovascular risk in HIV-infected patients (4) could also be clinically relevant. However, these results contradict the increase in sCD14 levels observed after MVC intensification in a recent study (14). In fact, the higher levels found in that study were statistically significant after 24 to 48 weeks, but not at 12 weeks, on cART, and the previous study included a very different set of patients (under an MVC intensification strategy, on suppressive cART, and with much higher CD4 ϩ T-cell levels than patients in the present work).…”
Section: Discussioncontrasting
confidence: 99%
“…The decrease of D dimer levels which have been associated with lower cardiovascular risk in HIV-infected patients (4) could also be clinically relevant. However, these results contradict the increase in sCD14 levels observed after MVC intensification in a recent study (14). In fact, the higher levels found in that study were statistically significant after 24 to 48 weeks, but not at 12 weeks, on cART, and the previous study included a very different set of patients (under an MVC intensification strategy, on suppressive cART, and with much higher CD4 ϩ T-cell levels than patients in the present work).…”
Section: Discussioncontrasting
confidence: 99%
“…[36][37][38][39] However, none of these studies was placebo-controlled, and subjects often improve their ART adherence when entering clinical trials, which may have explained the reduction in low-level viremia experienced by placebo-treated subjects in our own trial and in another recently reported intensification study. 40 The apparent reduction in T-cell activation during maraviroc intensification reported in the uncontrolled AIDS clinical trials group study (A5256) was also primarily driven by declines in CD38 expression, whereas HLA-DR expression actually increased significantly (which is largely consistent with our results), and neither of those changes were confirmed when retesting cryopreserved PBMCs from that trial.…”
Section: Discussionmentioning
confidence: 99%
“…We combined the data of two pilot open-label phase II clinical trials to evaluate the effect of maraviroc (ERRAD-VIH-01 (MRV): NCT00795444) 30 and raltegravir (ERRADVIH-02 (RAL): NCT00807443) 31 on the HIV latent reservoir. The studies were conducted at the Hospital Universitario Ram on y Cajal in Madrid, Spain, between 2008 and 2010.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…30,31 Briefly, PBMCs were isolated by Ficoll density gradient centrifugation (Lymphocytes Isolation Solution, Rafer, S.L., Zaragoza, Spain) from 300 mL of heparinised whole blood. Resting CD4 þ T-cells (CD3 þ /CD4 þ / HLADR À /CD25 À ) were then isolated and purified using magnetic beads according to the manufacturer's recommendations (Miltenyi Biotec GmbH., Bergisch Gladbach, Germany).…”
Section: Estimation Of the Hiv Latent Reservoirmentioning
confidence: 99%